2002
DOI: 10.1097/00075197-200203000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of conversion of α-linolenic acid to long chain n-3 fatty acids in man

Abstract: Alpha-linolenic acid (18:3n-3) is the major n-3 (omega 3) fatty acid in the human diet. It is derived mainly from terrestrial plant consumption and it has long been thought that its major biochemical role is as the principal precursor for long chain polyunsaturated fatty acids, of which eicosapentaenoic (20:5n-3) and docosahexaenoic acid (22:6n-3) are the most prevalent. For infants, n-3 long chain polyunsaturated fatty acids are required for rapid growth of neural tissue in the perinatal period and a nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
280
1
14

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(300 citation statements)
references
References 38 publications
5
280
1
14
Order By: Relevance
“…The levels of 22:6n-3 in captive-living anthropoid populations were significantly higher than those of their wild-living superfamily counterparts. Data from humans (Brenna, 2005;Francois et al, 2003) and baboons (Greiner et al, 1997;Su et al, 2005) also support the hypothesis that 22:6n-3 levels in milk increase with an increased source of preformed 22:6n-3.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The levels of 22:6n-3 in captive-living anthropoid populations were significantly higher than those of their wild-living superfamily counterparts. Data from humans (Brenna, 2005;Francois et al, 2003) and baboons (Greiner et al, 1997;Su et al, 2005) also support the hypothesis that 22:6n-3 levels in milk increase with an increased source of preformed 22:6n-3.…”
Section: Discussionmentioning
confidence: 79%
“…18:2n-6 is the precursor for all omega-6 (n-6) PUFA, including arachidonic acid (AA, and 18:3n-3 is the precursor for all omega-3 (n-3) PUFA including docosahexaenoic acid (DHA,. Biosynthesis of LCPUFA from PUFA precursors will depend on both the quantity of 18:2n-6 and 18:3n-3 in the diet (Jensen et al, 1995;Carlson, 1999;Brenna, 2005), the ratio of n-3 to n-6 PUFA in the diet (Huang and Brenna, 2001;Brenna, 2005) and the ability to convert n-3 and n-6 PUFA into their longer chain metabolites (Agostoni et al, 2001;Carlson, 2001;Brenna, 2005). Variation in conversion efficiency among species may produce different LCPUFA milk fatty acid composition despite similar dietary intakes of n-3 and n-6 PUFA precursors.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion from C 18 : 3n-3 (α-linolenic acid) to C 20 : 5n-3 has been demonstrated to range between 8 and 20 %, while conversion from C 18 : 3n-3 to C 22 : 6n-3 is even lower, i.e. 0·5-9 % (49)(50)(51) . The interaction between certain PUFA types and families, such as C 20 : 5n-3 and C 20 : 3n-6, can determine the effect produced on cell survival and neoplastic development.…”
Section: Lipid Profile and Tumour Cell Survivalmentioning
confidence: 99%
“…2. The human metabolism has a trivial ability to increase DHA given extra a-linolenic acid in the diet (Bézard et al 1994;Brenna 2002;Burdge and Calder 2005;Harper et al 2006), although levels of DHA in the serum of self-reported vegans is higher than expected, which if accurate suggests regulation of DHA levels and enhanced endogenous synthesis of DHA in the absence of dietary intake (Welch et al 2010). The starting ratio of shorter-chain n-6 to n-3 PUFA in the diet largely determines the ratio of longer-chain PUFA that are synthesised, and the ratio stored in tissues or cholesteryl-esters is Table 2.…”
Section: Components Of Animal Fat With Known Health Benefitsmentioning
confidence: 99%